Malaysia’s 40 years of Look East Policy and relocation of Indonesia’s capital: serumpun solution in Sarawak-West Kalimantan cross-border halal hub and relations - Ahmad Sharif Haron,; Zarina Othman,; Andika Wahab,; Irwan Syazli Saidin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The relocation of Indonesia's new capital to Kota Nusantara (East Kalimantan) is a game changer. It creates a spill-over of the prosper thy neighbour policy upon the existing West Kalimantan-Malaysia Sarawak border for the first Japanese AEON Big in Kuching (Malaysia's Sarawak) and potential Halal Wagyu beef market in Pontianak (Indonesia's West Kalimantan). Both countries should seize this golden opportunity to revisit their respective Look East Policy (LEP) with Japan and integrate Japan's advantages in quality assurance to overcome different regulatory Halal practices. After all, sustaining the Halal economy is no longer determined by the growing Muslim population alone but a shared knowledge and mutual policy lessons on Halal regulations and quality assurance. While both countries are essential players in the global halal hub and shared trade borders, there needs to be more harmonisation between Kalimantan-Sarawak's cross-border halal framework. With the Indonesian decision to relocate to a new capital, Kota Nusantara (located in East Kalimantan), there is a severe immediate need to bring LEP's benefits and profile the existing business ecosystem in Kuching (the capital of Sarawak) and Pontianak (capital of West Kalimantan).